(untitled) (diségno, 2024)
This contribution concentrates on a peculiar category of analogical models made of (movable) paper already present in scientific treatises from the 13th century onwards. If the first animated pages, capable of showing three-dimensional models, initially supported various fields of knowledge (gnomonic, perspective, astronomy, cryptography, the art of memory, anatomy, etc.), from the 18th century they became objects of entertainment, more markedly recreational, however for an adult public until the late 19th century. Paper models that could be folded to form volumes mainly concerned areas of knowledge related to geometry and gnomonic, as if to denounce how the written word and drawing were insufficient for the description of complex entities in space. One of the movable techniques, the pop-up, was the subject of a workshop, partly inspired by the experiences of Origamic Architecture. The didactic experience will be described using two approaches: first emphasising the importance of being able to obtain a not entirely predictable model through cutting and folding operations and, secondly, describing the subsequent representation of the same model through the methods of drawing and surveying. The experience indirectly created links with the subject of design, ideally moving from the abstract form made of paper to its materialisation in the construction field.